How do structural and agent-based factors influence the effectiveness of incentive policies? A spatially explicit agent-based model to optimize woodland-for-water PES policy design at the local level - Eulàlia Baulenas (Resilience Alliance, 2021)
A key factor in the resilience of water and forest ecosystems in the face of climate variability is the management decisions taken by the individuals responsible for them, from public officials to private owners. The presence of economic and other non-material incentives can modify the decision-making processes of these individuals and thereby avoid current socioeconomic trends in Mediterranean forested areas such as land abandonment and its detrimental consequences for both social and ecological systems. In this article, we created a spatially explicit agent-based model to observe the effects of the implementation of a woodland-for-water payment for ecosystem services scheme in a local area in Catalonia (NE Spain). The results of the model show that the policy design that supports recurrent management practices obtains the same results at the 25-year mark that other policy designs at the end of the modeled period in number of managed hectares. This design entails the presence of a local intermediary, financial coverage of the management changes to improve water conditions, and the targeting of only one environmental goal, thereby avoiding the ecosystem trade-offs that can arise when two or more goals are targeted. In this design, the first generation of forest owners engaging in behavior change would benefit from their actions, which is also key for maintaining their engagement with the payments for ecosystem services scheme.